Hollow fiber warm-keeping flocculus and preparation method thereof
By combining hollow polyester staple fibers with wool fibers and using furan-based polyester and polyquaternary ammonium salt-modified graphene for co-spinning, hollow fiber thermal insulation flakes were prepared. This solved the structural stability and electrostatic accumulation problems of the flake material, achieved good hygroscopicity and antistatic properties, and improved the comfort and mechanical properties of the flakes.
Patent Information
- Application Number
- CN202510673517.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-09-05
AI Technical Summary
Traditional flake materials have defects in structural stability and static electricity. The fiber bonding strength is insufficient and easy to slip. The tensile and compression resistance is poor, and static electricity accumulation leads to reduced comfort and functionality.
Hollow fiber thermal insulation flakes were prepared by combining hollow polyester staple fibers with wool fibers and co-spinning with furan-based polyester and polyquaternary ammonium salt-modified graphene. The polarity of the furan group and the steric hindrance of the polyquaternary ammonium salt were used to improve the hygroscopicity and antistatic properties.
It improves the hygroscopicity and antistatic properties of the flakes, maintains comfort and warmth, reduces static electricity accumulation, enhances the friction and entanglement points between fibers, and improves the structural stability and mechanical properties of the material.
Smart Images

Figure BDA0005417120920000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional nonwovens, and particularly relates to a hollow fiber thermal insulation flake and a preparation method thereof. Background Art
[0002] Batting, a sheet-like insulation material composed of a collection of fibers, is an important functional filling material in the modern textile industry. Based on the raw material source, batting can be divided into three categories: natural fibers (such as cotton, wool, and silk), regenerated fibers (such as viscose and lyocell), and synthetic fibers (such as polyester, acrylic, and polyamide). Its thermal insulation performance relies primarily on the fiber's thermal conductivity and the material's porous structure. This unique structure effectively blocks air convection, significantly reducing heat conduction efficiency and achieving excellent thermal insulation performance.
[0003] However, traditional flocculent materials still have several technical drawbacks: First, in terms of structural stability, traditional spray-bonded cotton uses a point-bonding process, resulting in insufficient inter-fiber bonding strength and prone to relative slippage, resulting in poor tensile and compression resistance, and structural collapse after repeated washing. Second, in terms of static electricity, the hydrophobic polymer segments in synthetic fiber flocculent materials lack charge conduction pathways, allowing static charges generated by friction to continuously accumulate, leading to the generation of static electricity during use. This phenomenon is particularly pronounced in dry environments, causing not only adsorption discomfort when worn but also a chain reaction in the material's functionality, affecting not only wearing comfort but also potentially deteriorating the fabric's breathability and moisture absorption.
[0004] Currently, the main approach to improving static electricity in flocculent materials is fiber functionalization: enhancing the fiber's antistatic properties through chemical or physical methods. For example, surface treatment or the addition of antistatic agents can reduce the generation and accumulation of static electricity. While these methods improve the fiber's antistatic properties to a certain extent, surface modification, which creates conductive pathways for charge leakage, often lacks mechanical durability. Summary of the Invention
[0005] The purpose of the present invention is to provide a hollow fiber thermal insulation flake and a preparation method thereof, so as to solve the problem that the hollow fiber thermal insulation flake has poor hygroscopicity.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The preparation method of the hollow fiber thermal insulation flakes comprises the following steps:
[0008] The furan-based polyester and polyquaternium salt-modified graphene are mixed, heated and blended, and the resulting melt is passed through a spinning pipe into a spinning manifold, and then melt-spun through a hollow spinneret to produce hollow polyester staple fibers. The furan-based polyester is prepared by esterification and polycondensation of a dibasic acid and a diol; the dibasic acid includes 2,5-furandicarboxylic acid and terephthalic acid.
[0009] The hollow polyester staple fibers and wool fibers are weighed, loosened, moistened, and evenly mixed, and then air-laid, laid, and needle-punched to obtain the hollow fiber thermal insulation flakes.
[0010] Furthermore, the spinning conditions are as follows: spinning temperature of 285±2°C, winding speed of 1200±2m / min, annular air speed of 4.0±0.2m / s, annular air temperature of 20±2°C, and draft ratio of 2.8 to 2.85; the acupuncture conditions are as follows: needle diameter of 0.8 to 1.0mm, acupuncture density of 20 to 35 needles / cm 2 .
[0011] Furthermore, the mass ratio of furan-based polyester and polyquaternary ammonium salt modified graphene is 100:0.2-2; the mass ratio of hollow polyester staple fiber and wool fiber is 70-80:20-30.
[0012] Furthermore, polyquaternium salt modified graphene is prepared by the following steps:
[0013] Under nitrogen protection, methacryloyloxyethyltrimethylammonium chloride was added to water, and then potassium persulfate as an initiator was added. The temperature was raised to 65-70°C and stirred for reaction for 6-8 hours. After the reaction was completed, the mixture was concentrated under reduced pressure to 50% of the original volume, precipitated with acetone, and dried in vacuum at 50°C to obtain a polyquaternium salt.
[0014] The polyquaternary ammonium salt is added into water respectively, graphene is added after stirring and dispersion, ultrasonic dispersion is carried out for 20-30 minutes, and then filtration is carried out, and drying is carried out at 160° C. for 6-8 hours to obtain the polyquaternary ammonium salt modified graphene.
[0015] Furthermore, the usage ratio of methacryloyloxyethyltrimethylammonium chloride, water and potassium persulfate is 16-18 mL:82-84 mL:0.4 g.
[0016] Furthermore, the mass ratio of the polyquaternary ammonium salt to the graphene is 1:10-15.
[0017] Furthermore, the molar ratio of the 2,5-furandicarboxylic acid to terephthalic acid is 3-7:3-7; and the molar ratio of the dibasic acid to the diol is 1:1.1-1.2.
[0018] Further, the furan-based polyester is prepared by the following steps:
[0019] The dibasic acid and diol are mixed, a catalyst is added, and an esterification reaction is carried out under nitrogen protection conditions: the temperature is raised to 230-250°C and the pressure is 300-360kPa. When the water output reaches 90% to 98% of the theoretical value, the pressure is released to normal pressure, and the esterification reaction is completed. The catalyst is tetrabutyl titanate, and the addition amount of tetrabutyl titanate is 0.1% of the molar amount of the dibasic acid;
[0020] After the esterification reaction is completed, the temperature is raised to 260-280° C., and a polycondensation reaction is carried out under vacuum conditions: the polycondensation reaction temperature is controlled to be 275° C., the vacuum degree is below 60 Pa, and the polycondensation reaction is carried out for 2-3 hours to obtain furan-based polyester.
[0021] Furthermore, the diol is one of ethylene glycol and 1,4-butanediol.
[0022] The hollow fiber thermal insulation flakes are prepared by the above-mentioned preparation method.
[0023] Beneficial effects of the present invention:
[0024] The invention provides a hollow fiber thermal insulation flake and a preparation method thereof. The flake is prepared from hollow polyester staple fibers and wool fibers as raw materials. The hollow polyester staple fibers are obtained by spinning after blending furan-based polyester and polyquaternium salt modified graphene. Furan groups are introduced into the furan-based polyester. The furan groups have certain polarity and can form hydrogen bonds with water molecules. This hydrogen bonding makes it easier for water molecules to be adsorbed on the polyester surface, thereby improving the hygroscopicity of the polyester, so that the flake can maintain good comfort and warmth retention in a humid environment, keep the surface charge distribution more uniform, and the charge is more easily conducted through the water film, thereby reducing the accumulation of static electricity and improving electrostatic properties. The introduction of polyquaternium salt, which is also a common antistatic agent, of furan rings can increase the steric hindrance of polymer segments. This steric hindrance can reduce the close packing between polymer segments, provide more space for quaternary ammonium salt molecules, thereby reducing the repulsive force between quaternary ammonium salt and polymer, and enhancing compatibility. Wool itself has good water and moisture absorption properties. The thermal insulation flakes prepared by combining it with hollow polyester staple fibers have good moisture absorption properties, thereby improving the antistatic properties of the flakes. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0026] The following is a detailed description of the hollow fiber thermal insulation flakes and their preparation methods in the embodiments of the present application.
[0027] The first aspect of the present invention provides a method for preparing a hollow fiber thermal insulation sheet, comprising the following steps:
[0028] The furan-based polyester and polyquaternium salt-modified graphene are mixed and heated to 250-290° C. for blending. The resulting melt is passed through a spinning pipe into a spinning manifold, and then melt-spun through a hollow spinneret to produce hollow polyester staple fibers.
[0029] Hollow polyester staple fibers and wool fibers are weighed, opened, moistened, and evenly mixed. The fibers are then air-laid, laid, and needle-punched to create the hollow fiber thermal insulation wadding. While wool fibers alone have poor resilience, combining them with hollow polyester staple fibers offers both good moisture absorption and resilience. Hollow polyester staple fibers are synthetic fibers with superior mechanical properties, such as abrasion resistance, compared to natural fibers like wool. Their combined use enhances the durability of the wadding while ensuring comfort.
[0030] In some specific embodiments, the spinning temperature is 285±2°C, the winding speed is 1200±2 m / min, the annular blowing speed is 4.0±0.2 m / s, the annular blowing temperature is 20±2°C, and the draft ratio is 2.8-2.85.
[0031] In some specific embodiments, the mass ratio of furan-based polyester and polyquaternium salt modified graphene is 100:0.2-2; the fineness of the hollow polyester staple fiber is 5.5 dtex; the fineness of the wool is 5.5 dtex;
[0032] The mass ratio of the hollow polyester staple fiber to the wool fiber is 70-80:20-30.
[0033] In some specific embodiments, the acupuncture conditions are: needle diameter 0.8-1.0 mm, acupuncture density 20-35 needles / cm 2 .
[0034] In some specific embodiments, the polyquaternary ammonium salt modified graphene is prepared by the following steps:
[0035] Under nitrogen protection, methacryloyloxyethyltrimethylammonium chloride is added to water, followed by the initiator potassium persulfate. The temperature is raised to 65-70°C and stirred for 6-8 hours. After the reaction, the mixture is concentrated under reduced pressure to 50% of the original volume, precipitated with acetone, and dried under vacuum at 50°C to obtain a polyquaternary ammonium salt. The ratio of methacryloyloxyethyltrimethylammonium chloride, water, and potassium persulfate is 16-18 mL: 82-84 mL: 0.4 g.
[0036] The polyquaternary ammonium salt is added into water respectively, graphene is added after stirring and dispersing, the mixture is ultrasonically dispersed for 20-30 minutes, filtered, and dried at 160° C. for 6-8 hours to obtain the polyquaternary ammonium salt modified graphene.
[0037] In some specific embodiments, the mass ratio of polyquaternary ammonium salt to graphene is 1:10-15.
[0038] In some specific embodiments, the furan-based polyester is prepared by esterification and polycondensation of a dibasic acid and a diol; the dibasic acid includes 2,5-furandicarboxylic acid and terephthalic acid; the molar ratio of the 2,5-furandicarboxylic acid to terephthalic acid is 3-7:3-7; and the molar ratio of the dibasic acid to the diol is 1:1.1-1.2.
[0039] In some specific embodiments, the furan-based polyester is prepared by the following steps:
[0040] The dibasic acid and diol are mixed, a catalyst is added, and an esterification reaction is carried out under nitrogen protection conditions: the temperature is raised to 230-250°C and the pressure is 300-360kPa. When the water output reaches 90% to 98% of the theoretical value, the pressure is released to normal pressure, and the esterification reaction is completed. The catalyst is tetrabutyl titanate, and the addition amount of tetrabutyl titanate is 0.1% of the molar amount of the dibasic acid;
[0041] After the esterification reaction is completed, the temperature is raised to 260-280° C., and a polycondensation reaction is carried out under vacuum conditions: the polycondensation reaction temperature is controlled to be 275° C., the vacuum degree is below 60 Pa, and the polycondensation reaction is carried out for 2-3 hours to obtain furan-based polyester.
[0042] In some specific embodiments, the diol is one of ethylene glycol and 1,4-butanediol.
[0043] In a second aspect of an embodiment of the present application, a hollow fiber thermal insulation sheet is provided, which is prepared by the above steps.
[0044] The following is a detailed description with reference to the embodiments.
[0045] Example 1
[0046] This embodiment provides a method for preparing a hollow fiber thermal insulation sheet, comprising the following steps:
[0047] The furan-based polyester and polyquaternium salt modified graphene were mixed, with the temperature of zone 1 at 260°C, zone 2 at 285°C, and zone 3 at 590°C; the mixture was blended, and the resulting melt was passed through a spinning pipe into a spinning manifold, and then melt-spun into hollow polyester staple fibers through a hollow spinneret; the spinning temperature was 285±2°C, the winding speed was 1200±2m / min, the annular air speed was 4.0±0.2m / s, the annular air temperature was 20±2°C, and the draft ratio was 2.8. The mass ratio of furan-based polyester and polyquaternium salt modified graphene was 100:1.2; the needle punching conditions were: needle diameter 1mm, needle punching density 20 needles / cm 2 ;
[0048] The hollow polyester staple fiber and wool fiber are weighed, opened, moistened, and evenly mixed, and then air-laid, laid, and needle-punched to obtain a hollow fiber thermal insulation flake. The fineness of the hollow polyester staple fiber is 5.5 dtex; the fineness of the wool is 5.5 dtex. The mass ratio of the hollow polyester staple fiber to the wool fiber is 70:30, and the surface density of the hollow fiber thermal insulation flake is 100 g / m 2 .
[0049] Polyquaternium salt modified graphene is prepared by the following steps:
[0050] Under nitrogen, methacryloyloxyethyltrimethylammonium chloride was added to water, followed by the initiator potassium persulfate. The temperature was raised to 65°C and stirred for 6 hours. After the reaction, the mixture was concentrated under reduced pressure to 50% of its original volume, precipitated with acetone, and dried under vacuum at 50°C to obtain a polyquaternary ammonium salt. The ratio of methacryloyloxyethyltrimethylammonium chloride, water, and potassium persulfate was 16 mL:84 mL:0.4 g.
[0051] Polyquaternary ammonium salt was added into water respectively, graphene was added after stirring and dispersion, ultrasonic dispersion was performed for 20 minutes, and then filtration was performed. The mixture was dried at 160° C. for 6 hours to obtain polyquaternary ammonium salt modified graphene. The mass ratio of polyquaternary ammonium salt to graphene was 1:10.
[0052] Furan-based polyesters are prepared by the following steps:
[0053] The dibasic acid and diol are mixed, a catalyst is added, and an esterification reaction is carried out under nitrogen protection conditions: the temperature is raised to 230°C and the pressure is 300 kPa. When the water output reaches 90% of the theoretical value, the pressure is released to normal pressure, and the esterification reaction is completed. The catalyst is tetrabutyl titanate, and the addition amount of tetrabutyl titanate is 0.1% of the molar amount of the dibasic acid. The dibasic acid includes 2,5-furandicarboxylic acid and terephthalic acid; the diol is ethylene glycol; the molar ratio of the 2,5-furandicarboxylic acid to terephthalic acid is 3:7; and the molar ratio of the dibasic acid to the diol is 1:1.1.
[0054] After the esterification reaction is completed, the temperature is raised to 275° C., and a polycondensation reaction is carried out under vacuum conditions: the polycondensation reaction temperature is controlled at 275° C., the vacuum degree is below 60 Pa, and the polycondensation reaction is carried out for 3 hours to obtain furan-based polyester.
[0055] Example 2
[0056] This embodiment provides a method for preparing a hollow fiber thermal insulation sheet, comprising the following steps:
[0057] The furan-based polyester and polyquaternium salt modified graphene were mixed, with the temperature of zone 1 being 260°C, the temperature of zone 2 being 285°C, and the temperature of zone 3 being 590°C; the mixture was blended, and the resulting melt was passed through a spinning pipe into a spinning manifold, and then melt-spun into hollow polyester staple fibers through a hollow spinneret; the spinning temperature was 285±2°C, the winding speed was 1200±2m / min, the annular air speed was 4.0±0.2m / s, the annular air temperature was 20±2°C, and the draft ratio was 2.8. The mass ratio of furan-based polyester and polyquaternium salt modified graphene was 100:0.4; the needle punching conditions were: needle diameter 1mm, needle punching density 20 needles / cm 2 ;
[0058] The hollow polyester staple fiber and wool fiber are weighed, opened, moistened, and evenly mixed, and then air-laid, laid, and needle-punched to obtain a hollow fiber thermal insulation flake. The fineness of the hollow polyester staple fiber is 5.5 dtex; the fineness of the wool is 5.5 dtex; the mass ratio of the hollow polyester staple fiber to the wool fiber is 70:30; the surface density of the hollow fiber thermal insulation flake is 100 g / m 2 .
[0059] The polyquaternary ammonium salt modified graphene is the same as that in Example 1.
[0060] The furan-based polyester is the same as that in Example 1.
[0061] Example 3
[0062] This embodiment provides a method for preparing a hollow fiber thermal insulation sheet, comprising the following steps:
[0063] The furan-based polyester and polyquaternium salt modified graphene were mixed, with the temperature of zone 1 at 260°C, zone 2 at 285°C, and zone 3 at 590°C; the mixture was blended, and the resulting melt was passed through a spinning pipe into a spinning manifold, and then melt-spun into hollow polyester staple fibers through a hollow spinneret; the spinning temperature was 285±2°C, the winding speed was 1200±2m / min, the annular air speed was 4.0±0.2m / s, the annular air temperature was 20±2°C, and the draft ratio was 2.8. The mass ratio of furan-based polyester and polyquaternium salt modified graphene was 100:1.8; the needle punching conditions were: needle diameter 1mm, needle punching density 20 needles / cm 2 ;
[0064] The hollow polyester staple fiber and wool fiber are weighed, opened, moistened, and evenly mixed, and then air-laid, laid, and needle-punched to obtain a hollow fiber thermal insulation flake. The fineness of the hollow polyester staple fiber is 5.5 dtex; the fineness of the wool is 5.5 dtex; the mass ratio of the hollow polyester staple fiber to the wool fiber is 70:30; the surface density of the hollow fiber thermal insulation flake is 100 g / m 2 .
[0065] The polyquaternary ammonium salt modified graphene is the same as that in Example 1.
[0066] The furan-based polyester is the same as that in Example 1.
[0067] Example 4
[0068] This embodiment provides a method for preparing a hollow fiber thermal insulation sheet, comprising the following steps:
[0069] The furan-based polyester and polyquaternium salt modified graphene were mixed, with the temperature of zone 1 at 260°C, zone 2 at 285°C, and zone 3 at 590°C; the mixture was blended, and the resulting melt was passed through a spinning pipe into a spinning manifold, and then melt-spun into hollow polyester staple fibers through a hollow spinneret; the spinning temperature was 285±2°C, the winding speed was 1200±2m / min, the annular air speed was 4.0±0.2m / s, the annular air temperature was 20±2°C, and the draft ratio was 2.8. The mass ratio of furan-based polyester and polyquaternium salt modified graphene was 100:1.2; the needle punching conditions were: needle diameter 1mm, needle punching density 20 needles / cm 2 ;
[0070] The hollow polyester staple fiber and wool fiber are weighed, opened, moistened, and evenly mixed, and then air-laid, laid, and needle-punched to obtain a hollow fiber thermal insulation flake. The fineness of the hollow polyester staple fiber is 5.5 dtex; the fineness of the wool is 5.5 dtex; the mass ratio of the hollow polyester staple fiber to the wool fiber is 70:30; the surface density of the hollow fiber thermal insulation flake is 100 g / m 2 .
[0071] Polyquaternium salt modified graphene is prepared by the following steps:
[0072] Under nitrogen, methacryloyloxyethyltrimethylammonium chloride was added to water, followed by the initiator potassium persulfate. The temperature was raised to 65°C and stirred for 6 hours. After the reaction, the mixture was concentrated under reduced pressure to 50% of its original volume, precipitated with acetone, and dried under vacuum at 50°C to obtain a polyquaternary ammonium salt. The ratio of methacryloyloxyethyltrimethylammonium chloride, water, and potassium persulfate was 18 mL:82 mL:0.4 g.
[0073] Polyquaternary ammonium salt was added into water respectively, graphene was added after stirring and dispersion, ultrasonic dispersion was performed for 20 minutes, and then filtration was performed. The mixture was dried at 160° C. for 6 hours to obtain polyquaternary ammonium salt modified graphene. The mass ratio of polyquaternary ammonium salt to graphene was 1:10.
[0074] The furan-based polyester is the same as that in Example 1.
[0075] Example 5
[0076] This embodiment provides a method for preparing a hollow fiber thermal insulation sheet, comprising the following steps:
[0077] The furan-based polyester and polyquaternium salt modified graphene were mixed, with the temperature of zone 1 at 260°C, zone 2 at 285°C, and zone 3 at 590°C; the mixture was blended, and the resulting melt was passed through a spinning pipe into a spinning manifold, and then melt-spun into hollow polyester staple fibers through a hollow spinneret; the spinning temperature was 285±2°C, the winding speed was 1200±2m / min, the annular air speed was 4.0±0.2m / s, the annular air temperature was 20±2°C, and the draft ratio was 2.8. The mass ratio of furan-based polyester and polyquaternium salt modified graphene was 100:1.2; the needle punching conditions were: needle diameter 1mm, needle punching density 20 needles / cm 2 ;
[0078] The hollow polyester staple fiber and wool fiber are weighed, opened, moistened, and evenly mixed, and then air-laid, laid, and needle-punched to obtain a hollow fiber thermal insulation flake. The fineness of the hollow polyester staple fiber is 5.5 dtex; the fineness of the wool is 5.5 dtex; the mass ratio of the hollow polyester staple fiber to the wool fiber is 70:30; the surface density of the hollow fiber thermal insulation flake is 100 g / m 2 .
[0079] The polyquaternary ammonium salt modified graphene is the same as that in Example 1.
[0080] Furan-based polyesters are prepared by the following steps:
[0081] The dibasic acid and the diol are mixed, a catalyst is added, and an esterification reaction is carried out under nitrogen protection conditions: the temperature is raised to 230°C and the pressure is 300 kPa. When the water output reaches 90% of the theoretical value, the pressure is released to normal pressure, and the esterification reaction is completed. The catalyst is tetrabutyl titanate, and the addition amount of tetrabutyl titanate is 0.1% of the molar amount of the dibasic acid. The dibasic acid includes 2,5-furandicarboxylic acid and terephthalic acid; the diol is ethylene glycol; the molar ratio of the 2,5-furandicarboxylic acid to terephthalic acid is 5:5; and the molar ratio of the dibasic acid to the diol is 1:1.1.
[0082] After the esterification reaction is completed, the temperature is raised to 275° C., and a polycondensation reaction is carried out under vacuum conditions: the polycondensation reaction temperature is controlled at 275° C., the vacuum degree is below 60 Pa, and the polycondensation reaction is carried out for 3 hours to obtain furan-based polyester.
[0083] Example 6
[0084] This embodiment provides a method for preparing a hollow fiber thermal insulation sheet, comprising the following steps:
[0085] The furan-based polyester and polyquaternium salt modified graphene were mixed, with the temperature of zone 1 at 260°C, zone 2 at 285°C, and zone 3 at 590°C; the mixture was blended, and the resulting melt was passed through a spinning pipe into a spinning manifold, and then melt-spun into hollow polyester staple fibers through a hollow spinneret; the spinning temperature was 285±2°C, the winding speed was 1200±2m / min, the annular air speed was 4.0±0.2m / s, the annular air temperature was 20±2°C, and the draft ratio was 2.8. The mass ratio of furan-based polyester and polyquaternium salt modified graphene was 100:1.2; the needle punching conditions were: needle diameter 1mm, needle punching density 20 needles / cm 2 ;
[0086] The hollow polyester staple fiber and wool fiber are weighed, opened, moistened, and evenly mixed, and then air-laid, laid, and needle-punched to obtain a hollow fiber thermal insulation flake. The fineness of the hollow polyester staple fiber is 5.5 dtex; the fineness of the wool is 5.5 dtex; the mass ratio of the hollow polyester staple fiber to the wool fiber is 70:30; the surface density of the hollow fiber thermal insulation flake is 100 g / m 2 .
[0087] The polyquaternary ammonium salt modified graphene is the same as that in Example 1.
[0088] Furan-based polyesters are prepared by the following steps:
[0089] The dibasic acid and diol are mixed, a catalyst is added, and an esterification reaction is carried out under nitrogen protection conditions: the temperature is raised to 230°C and the pressure is 300 kPa. When the water output reaches 90% of the theoretical value, the pressure is released to normal pressure, and the esterification reaction is completed. The catalyst is tetrabutyl titanate, and the addition amount of tetrabutyl titanate is 0.1% of the molar amount of the dibasic acid. The dibasic acid includes 2,5-furandicarboxylic acid and terephthalic acid; the diol is ethylene glycol; the molar ratio of the 2,5-furandicarboxylic acid to terephthalic acid is 7:3; and the molar ratio of the dibasic acid to the diol is 1:1.1.
[0090] After the esterification reaction is completed, the temperature is raised to 275° C., and a polycondensation reaction is carried out under vacuum conditions: the polycondensation reaction temperature is controlled at 275° C., the vacuum degree is below 60 Pa, and the polycondensation reaction is carried out for 3 hours to obtain furan-based polyester.
[0091] Comparative Example 1
[0092] Compared with Example 1, this comparative example replaces the polyquaternary ammonium salt-modified graphene with graphene, and the remaining raw materials and preparation process remain the same as those in Example 1.
[0093] Comparative Example 2
[0094] Compared with Example 1, the raw material ratio of the polyquaternary ammonium salt modified graphene in this comparative example is different, and the usage ratio of methacryloyloxyethyltrimethylammonium chloride, water and potassium persulfate is 30 mL:70 mL:0.4 g; the other raw materials and preparation process remain the same as in Example 1.
[0095] Comparative Example 3
[0096] This comparative example is pure wool.
[0097] Performance tests were conducted on Examples 1-6 and Comparative Examples 1-3. The breaking strength of the samples was measured according to GB / T 24218.3-2010. Hygroscopicity (% regain) was tested according to GB / T 6529-2008, "Standard Atmospheres for Conditioning and Testing Textiles." Wrinkle resistance was tested according to GB / T 3819-1997, "Determination of Crease Recovery of Textiles - Recovery Angle Method." The results are shown in Table 1.
[0098] Table 1
[0099]
[0100] As shown in Table 1, better hygroscopicity allows water to be absorbed more easily into the fiber pores or adsorbed onto the fiber surface. These properties enable the flakes to maintain excellent comfort and warmth in humid environments, maintain a more uniform surface charge distribution, and facilitate charge conduction through the water film, thereby reducing static electricity accumulation and improving electrostatic performance. Test results indicate that optimizing furan-based polyester and polyquaternium salt-modified graphene can appropriately improve hygroscopicity.
[0101] In the embodiment 1-embodiment 6 in the present application, take furan-based polyester and polyquaternium salt modified graphene as raw material, the hollow polyester staple fiber obtained by blending, these two-dimensional sheet structures can form tiny projection or uneven region in polyester matrix.These tiny projections can increase the roughness of fiber surface, thereby increase the frictional force between fiber, and the frictional force between hollow polyester staple fiber and fiber strengthens, and can make the interfiber entanglement point increase, so the brute force of fiber web increases thereupon, and selects undressed Graphene in comparative example 1, easily reunite in the resin matrix of furan-based polyester, cause the dispersibility of raw material poor, influence mechanical property.And changed the polyquaternium salt modified graphene in comparative example 2, can cause the intrinsic viscosity of polyquaternium salt to be too large, increase the viscosity difference between resin matrix, cause phase separation, influence polyquaternium salt modified graphene at furan-based polyester dispersibility, and then cause the mechanical property of material to decline. In terms of breaking strength, pure wool has advantages such as good elasticity and large curl. The flakes in the present invention can maintain properties similar to those of pure wool and maintain good wrinkle resistance.
[0102] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.
[0103] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a hollow fiber thermal insulation sheet, characterized in that: The steps include: The furan-based polyester and polyquaternium salt-modified graphene are mixed, heated and blended, and the resulting melt is passed through a spinning pipe into a spinning manifold, and then melt-spun through a hollow spinneret to produce hollow polyester staple fibers. The furan-based polyester is prepared by esterification and polycondensation of a dibasic acid and a diol; the dibasic acid includes 2,5-furandicarboxylic acid and terephthalic acid. The hollow polyester staple fibers and wool fibers are weighed, loosened, moistened, and evenly mixed, and then air-laid, laid, and needle-punched to obtain the hollow fiber thermal insulation flakes.
2. The method for preparing the hollow fiber thermal insulation sheet according to claim 1, characterized in that: The spinning conditions are as follows: spinning temperature 285±2°C, winding speed 1200±2m / min, annular air speed 4.0±0.2m / s, annular air temperature 20±2°C, and draft ratio 2.8-2.85; the needle punching conditions are as follows: needle diameter 0.8-1.0mm, and needle punching density 20-35 needles / cm 2 .
3. The method for preparing the hollow fiber thermal insulation sheet according to claim 1, characterized in that: The mass ratio of furan-based polyester and polyquaternary ammonium salt modified graphene is 100:0.2-2; the mass ratio of hollow polyester staple fiber and wool fiber is 70-80:20-30.
4. The method for preparing the hollow fiber thermal insulation sheet according to claim 1, characterized in that: Polyquaternium salt modified graphene is prepared by the following steps: Under nitrogen protection, methacryloyloxyethyltrimethylammonium chloride is added to water, and then potassium persulfate as an initiator is added. The temperature is raised to 65-70°C and stirred for reaction for 6-8 hours. After the reaction is completed, the mixture is concentrated under reduced pressure to 50% of the original volume, precipitated with acetone, and vacuum dried to obtain a polyquaternium salt. The polyquaternary ammonium salt is added into water respectively, graphene is added after stirring and dispersing, the mixture is ultrasonically dispersed for 20-30 minutes, filtered, and dried at 160° C. for 6-8 hours to obtain the polyquaternary ammonium salt modified graphene.
5. The method for preparing the hollow fiber thermal insulation sheet according to claim 4, characterized in that: The usage ratio of methacryloyloxyethyltrimethylammonium chloride, water and potassium persulfate is 16-18 mL:82-84 mL:0.4 g.
6. The method for preparing the hollow fiber thermal insulation sheet according to claim 4, characterized in that: The mass ratio of polyquaternary ammonium salt to graphene is 1:10-15.
7. The method for preparing the hollow fiber thermal insulation sheet according to claim 1, characterized in that: The molar ratio of the 2,5-furandicarboxylic acid to terephthalic acid is 3-7:3-7; the molar ratio of the dibasic acid to the diol is 1:1.1-1.
2.
8. The method for preparing the hollow fiber thermal insulation sheet according to claim 1, characterized in that: Furan-based polyesters are prepared by the following steps: The dibasic acid and diol are mixed, a catalyst is added, and an esterification reaction is carried out under nitrogen protection conditions: the temperature is raised to 230-250°C and the pressure is 300-360kPa. When the water output reaches 90% to 98% of the theoretical value, the pressure is released to normal pressure, and the esterification reaction is completed. The catalyst is tetrabutyl titanate, and the addition amount of tetrabutyl titanate is 0.1% of the molar amount of the dibasic acid; After the esterification reaction is completed, the temperature is raised to 260-280° C., and a polycondensation reaction is carried out under vacuum conditions: the polycondensation reaction temperature is controlled to be 275° C., the vacuum degree is below 60 Pa, and the polycondensation reaction is carried out for 2-3 hours to obtain furan-based polyester.
9. The method for preparing the hollow fiber thermal insulation sheet according to claim 8, characterized in that: The diol is one of ethylene glycol and 1,4-butanediol.
10. Hollow fiber thermal insulation sheet, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9.